ANALISIS PENGARUH KONSUMSI RUMAH TANGGA, INVESTASI DAN BELANJA PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI NUSA TENGGARA BARAT - Sanjani, Muhammad Rafi'i (Politeknik Bisnis Indonesia, 2024)
This study aims to determine the influence of household consumption, investment and government spending on economic growth in West Nusa Tenggara (WNT) in 2017-2021. This study uses panel data regression consisting of 10 districts in West Nusa Tenggara (WNT) using the eviews 12 program. The data used is secondary data sourced from the official website of the Central Statistics Agency (CSA) and the Investment and One-Stop Service Office (IOSSO) West Nusa Tenggara (WNT) 2017-2021. The estimation used in this study is the Common Effect Model (CEM). Overall, the results of the panel data regression analysis and hypothesis testing concluded that in this study simultaneously household consumption, investment, and government spending has a positive but not significant effect on economic growth. The household consumption variable has a positive but not significant effect on economic growt. Investment partially has a positive but not significant effect on economic growt. And goverment spanding partially has a negative but not significant effect oneconomic growot.